The Influence of E-Service Quality on Customer Satisfaction and Loyalty in Online Transportation Applications - Revi Kristioni; Rayesha Putra Baistama; Indra Widjaja (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
This article aims to investigate the mechanisms underlying the relationship between e-service quality, customer satisfaction, and customer loyalty in online transportation applications. This study adopts relevant theoretical approaches, including customer satisfaction theory and loyalty theory, to analyze the role of e-service quality in driving satisfaction and loyalty. By involving 400 respondents who are users of online transportation applications, the research results show that e-service quality has a significant and positive impact on customer satisfaction and customer loyalty. In addition, customer satisfaction also proved to mediate the relationship between e-service quality and customer loyalty, although the mediating effect was smaller compared to the direct effect.